Photogrammetric block adjustment without control points - El-Ashmawy, Khalid L. A. (Geodesy and Cartography, 2018)
A simple method for close range and aerial photogrammetry applications has been developed. The method is in the form of bundle block adjustment which utilizes only the measured distance(s) between points for generating adjusted relative three dimensional (3D) coordinate system. Software based on the proposed method has been developed and tested using simulated data. The effects of block size, number and location of measured distances, and random errors on bundle block adjustments using the proposed and the conventional methods have been studied using simulated and actual photogrammetric data. It was found that the accuracy of the bundle block adjustment using the proposed method is comparable or better than the results of conventional method. The proposed method, is suitable for photogrammetrists and non-photogrammetrists in different fields such as architectural, archaeological, forensic and aerial photogrammetry, where relative 3D coordinates system may be required. It has a significant effect on reducing the overall cost of the photogrammetric project. Merging the capabilities of the developed software and Computer Aided Design (CAD) technology, especially 3D drawing generation, widens its applications areas to include recording buildings and monuments which is necessary for architectural and archaeological applications.